Short‐Term Immunogenicity and Safety of an Accelerated Pre‐Exposure Prophylaxis Regimen With Japanese Encephalitis Vaccine in Combination With a Rabies Vaccine: A Phase III, Multicenter, Observer‐Blind Study. Issue 4 (22nd May 2015) - Jelinek, Tomas; Burchard, Gerd D.; Dieckmann, Sebastian; Bühler, Silja; Paulke‐Korinek, Maria; Nothdurft, Hans D.; Reisinger, Emil; Ahmed, Khaleel; Bosse, Dietrich; Meyer, Seetha; Costantini, Marco; Pellegrini, Michele
<x xml:space="preserve">Abstract</x> Background The current Japanese encephalitis (JE) vaccination regimen requires two doses and 4 weeks to complete, which may not always be feasible for travelers on short notice. One of the primary endpoints of this phase III study was to demonstrate noninferiority of immune responses to a JE vaccine following an accelerated 1‐week JE vaccination regimen administered concomitantly with a rabies vaccine as compared to a standard 4‐week JE regimen alone. In addition, the immunogenicity of concomitant administration of JE and rabies vaccines following standard regimens was evaluated, as well as the tolerability and safety profile of each regimen under study. Methods Healthy adults aged 18 to ≤65 years were randomized to regimens with an accelerated or standard schedule: JE+rabies‐standard (n = 167), JE+rabies‐accelerated (n = 217) or JE‐standard (n = 56). Immunogenicity against JE antigen was assessed by a 50% plaque reduction neutralization test (PRNT50) titer of ≥1 : 10, measured 28 days after last active vaccine (LAV) administration. Solicited reactions were collected 7 days after each vaccination; spontaneously reported adverse events (AEs) and serious AEs were monitored up to day 57. This paper reports results until day 57. Results Noninferiority of immune responses was established for JE+rabies‐accelerated compared to the JE‐standard regimen 28 days after LAV administration. Overall, 99% and 100% of subjects in the JE+rabies‐accelerated and JE‐standard groups, respectively, achieved PRNT50 titers of ≥1 : 10 at 28 days after LAV administration. No impact of concomitant rabies vaccination was observed either on immune responses or on the safety profile of the JE vaccine. Conclusions This was the first randomized, controlled trial that demonstrated the strong short‐term immunogenicity of a new, accelerated, 1‐week JE‐regimen, which was noninferior to that of the standard regimen, with a satisfactory tolerability and safety profile and no impact of concomitant rabies vaccination. This accelerated regimen, if licensed, could potentially be a valid alternative for individuals requiring a primary series of JE vaccination and rabies pre‐exposure prophylaxis on short notice.